(untitled) (Medical Forum Monthly, 2022)
ABSTRACT Objective: To determine the frequency of weight gain in children of probable Tuberculosis under treatment. Study Design: Descriptive case series study Place and Duration of Study: This study was conducted at the TB DOTS Clinic, CMC Children Hospital, Larkana from July 2017 to January 2019. Materials and Methods: Total 100 children of age 6 months to 5 years age, both genders and new cases of probable tuberculosis were consecutively selected. Children with malnutrition, complain of Refusal to feed, convulsions, unconsciousness or having HIV co-infection were excluded. Results: Mean age ± SD was 33.53 ± 12.56 months. (Ranged 07-60 months). Mean ± SD initial weight was 18.75 ± 6.33 Kgs while mean ± SD final weight was 25.36 ± 9.23 Kgs. Overall, net minimum & maximum weight gain were 0.5 to 15.6 Kgs with mean ± SD weight gain of 9.61 ± 4.03 Kgs. Male children were in almost two third majority i-e; 63% (n= 63). Sixty percent (60%, n= 60) children had confirmed tuberculosis. Weight gain in probable cases of TB after treatment given was found to positive among seventy nine percent (n= 79) children. The stratification analysis showed that frequency of weight gain increased with increasing age, male children, rural living children and with taking four ATT drugs. Conclusion: Tuberculosis is a great burden among our population especially children in whom diagnosis is difficult or late. Weight gain is main indicator of successful treatment. The current study highlighted the importance of TB occurrence in children by investigating one of its core issues. Further studies are warranted to understand other changing phenomenon of presentations, diagnosis and treatment effectiveness and compliance.